Biografías. (2000)
Biografía de los arquitectos integrantes de los siguentes estudios. <Bearth & Deplazes Architekten>, <Gerstlauer-Molne> y <Jüngling & Hagmann>
Keywords: BIOGRAFIAS; BEARTH, VALENTIN; DEPLAZES, ANDREA; CAMINADA, GION A; JÜNGLING, DIETER; CONZETT, JÜRG; GERSTLAUER, ROLF; MOLNE, INGER; HAGMANN, ANDREAS; KEREZ, CHRISTIAN; SUIZA; GRAUBÜNDEN